2022
DOI: 10.3390/cells11244031
|View full text |Cite
|
Sign up to set email alerts
|

FUT2 Facilitates Autophagy and Suppresses Apoptosis via p53 and JNK Signaling in Lung Adenocarcinoma Cells

Abstract: Lung cancer is the most common cancer with high morbidity and mortality worldwide. Our previous studies showed that fucosyltransferase 2 (FUT2) is highly expressed in lung adenocarcinoma (LUAD) and plays a vital role in the tumorigenesis of LUAD. However, the underlying mechanism is not fully understood. Autophagy has recently attracted increasing attention due to its pro-survival role in cancer progression and metastasis. Here, we found that FUT2 was up-regulated and had an AUC (Area Under Curve) value of 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…35 The tumor suppressor p53 and its associated p53 signaling pathway have been implicated in mediating the progression of various cancers such as breast cancer, 36 pancreatic cancer, 37 and lung cancer. 38 The study by Zhang et al 39 found that activation of the p53 signaling pathway can effectively promote autophagy in LUAD cells and inhibit apoptosis of cancer cells. Glutamine is a conditionally essential amino acid crucial for cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The tumor suppressor p53 and its associated p53 signaling pathway have been implicated in mediating the progression of various cancers such as breast cancer, 36 pancreatic cancer, 37 and lung cancer. 38 The study by Zhang et al 39 found that activation of the p53 signaling pathway can effectively promote autophagy in LUAD cells and inhibit apoptosis of cancer cells. Glutamine is a conditionally essential amino acid crucial for cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“… 38 The study by Zhang et al. 39 found that activation of the p53 signaling pathway can effectively promote autophagy in LUAD cells and inhibit apoptosis of cancer cells. Glutamine is a conditionally essential amino acid crucial for cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…FUT1 expression has been correlated with treatment outcomes in LUAD patients receiving epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) ( 73 ). FUT2 is overexpressed in LUAD and may facilitate autophagy and suppress apoptosis via the p53 and JNK pathways ( 74 ), as well as induce EMT through TGF-β/Smad signaling in LUAD ( 75 ). FUT4 expression shows a negative correlation with the overall survival in operable LUAD ( 113 , 114 ), and may induce lung colonization and distant metastases of lung cancer cells ( 114 ).…”
Section: Glycoenzyme-based Protein Glycosylation Changes In Crdsmentioning
confidence: 99%
“…The top genes that correlated with histologic severity (Nancy score 35 ) included proinflammatory genes SAA1, S100A8, S100A9; myeloid cell-associated genes TREM1, LILRA5; neutrophil chemotactic genes FPR1, FPR2, CXCL1, CXCR1, CXCR2, FCGR3B/CD16; hypoxia related gene HIF1A; autophagy gene DRAM1 and unfolded protein response gene XBP1 (Fig. 1i) [36][37][38][39] .The findings from our EC-bulk transcriptomic data revealed a complex, myeloid cell-dominated milieu in UCassociated inflammation that significantly correlated with parameters of clinical, endoscopic, and histologic severity.…”
Section: Intraepithelial Immune Compartment Is Extensively Remodeled ...mentioning
confidence: 99%